The Influence of Student’s Language Learning Strategies Used towards Their Achievement in Structure IV - Dwiniasih, Dwiniasih (Universitas Swadaya Gunung Jati, 2015)
This study was aimed to know the influence of student’s language learningstrategies used towards their achievement in structure IV and the most strategy used. It is done in responding the fact, most of the students do not aware of their learning strategies. It makes them difficult understanding the knowledge transferred. By using descriptive method, this study used document test and SILL questionnaire as the instrument of the data. Meanwhile, in analyzing the data collected, the writer used SPSS simple linear regression (Muijs.200:143). The result of the study showed the influence of L2 student’s strategies is significantly weak towards their achievement in structure IV. While the most strategies used was metacognitive strategy. It is because so many factors influence student’s achievement, such as student’s ability, learning style, and teacher’s methodology used. Therefore, it is teacher’s task to motivate students aware of learning strategy used, so they could get well understanding.